A Process Algebraic Description of a Temporal Wireless Network Protocol - Bhandal, Colm; Bouroche, Melanie; Hughes, Arthur (Electronic Communications of the EASST, 2011)
The problem of coordination is central to research in robotics, automatically guided vehicles, autonomous cars, unmanned aerial vehicles, and any other areas in which autonomous agents of any kind operate concurrently. This paper focuses on one particular model of coordination, namely Comhord´u. The contribution of this work is a formalisation of the existing model in precise mathematical terms. This formalisation extends our understanding of the model and provides a basis for future work such as the formal verification of model properties, e.g. system safety.